Divine assemblies in early Greek and Mesopotamian narrative poetry - Ballesteros Petrella, B (2017)
This thesis charts divine assembly scenes in ancient Mesopotamian narrative poetry and the early Greek hexameter corpus, and aims to contribute to a cross-cultural comparison in terms of literary systems. The recurrent scene of the divine gathering is shown to underpin the construction of small- and large-scale compositions in both the Sumero-Akkadian and early Greek traditions. Parts 1 and 2 treat each corpus in turn, reflecting a methodological concern to assess the comparanda within their own context first. Part 1 (Chapters 1-4) examines Sumerian narrative poems, and the Akkadian narratives Atra-ḫasīs, Anzû, Enūma eliš, Erra and Išum and the Epic of Gilgameš. Part 2 (Chapters 5-8) considers Homer's Iliad, the Odyssey, the Homeric Hymns and Hesiod's Theogony. The comparative approaches in Part 3 are developed in two chapters (9-10). Chapter 9 offers a detailed comparison of this typical scene's poetic morphology and compositional purpose. Relevant techniques and effects, a function of the aural reception of literature, are shown to overlap to a considerable degree. Although the Greeks are unlikely to have taken over the feature from the Near East, it is suggested that the Greek divine assembly is not to be detached form a Near Eastern context. Because the shared elements are profoundly embedded in the Greek orally-derived poetic tradition, it is possible to envisage a long-term process of oral contact and communication fostered by common structures. Chapter 10 turns to a comparison of the literary pantheon: a focus on the organisation of divine prerogatives and the chief god figures illuminates culture-specific differences which can be related to historical socio-political conditions. Thus, this thesis seeks to enhance our understanding of the representation of the gods in Mesopotamian poetry and early Greek epic, and develops a systemic approach to questions of transmission and cultural appreciation.